A Systems Approach to Estimating the Natural Rate of Unemployment and Potential Output for the United States. (IMF Working Papers; Working Paper ;, 1989)
The methodology used in this paper has three distinguishing features: the natural rate of unemployment and potential output are jointly estimated; estimation integrates wage and price data with 'real' and structural data; and third, the methodology encompasses many of the methods found in the literature. The results indicate that potential output growth has recovered somewhat during the early 1980s, but remains below the rapid rates of increase in the late 1960s. The natural rate, after rising during the late 1960s and the 1970s, is found to have declined in the 1980s. The paper concludes with an assessment of medium-term prospects for potential output and-the natural rate.